Augmented Reality in Education: A Comprehensive Analysis of Transformative Learning Technologies - Kancharla, Soma Sundar Reddy (International Journal of Computing and Engineering, 2025)
Augmented Reality (AR) is a groundbreaking technological paradigm that will redefine educational processes in various subjects. This article explores the advanced algorithms, diverse applications, and far-reaching implications of AR technologies within modern learning and instructional settings. By fusing cutting-edge computing architectures with advanced pedagogical theory, AR technologies develop highly interactive, adaptively responsive learning environments that break beyond conventional pedagogical constraints. The investigation spans essential aspects ranging from technological infrastructure to disciplinary uses, implementation issues, and directions for the future, uncovering the incredible potential of AR to reform knowledge transmission methods. Interdisciplinary insights highlight AR's ability to produce customized, interactive learning experiences that essentially reinterpret cognitive engagement in scientific, historical, medical, and technical contexts.